REGIONAL CENTERS OF POWER AND THEIR EURASIAN POLITICS (Rivalry in the Islamic East— The Turkish Vector) - VARBANETS, Pavel (CENTRAL ASIA AND THE CAUCASUS, 2008)
In the last twenty years, the international relations system has undergone major changes, however, contrary to America’s expectations, the bipolar world order that disappeared together with the Soviet Union and the end of the Cold War was not replaced with a unipolar world. Today, international processes are somewhat chaotic, which explains the appearance of several poles of power—the United States, EU, Russia, Southeast Asia, and the Islamic world. While in the West the rivalry over spheres of influence is drawing to an end and a new order has all but emerged, the Islamic world is only just being drawn into the process. There is the opinion in the expert community that the Muslim world will change its makeup and the Arabic domination of today will be replaced with a new system concentrated around new centers of power such as Turkey and Iran. The former is claiming the role of a regional leader in the Islamic East due to several new circumstances: it enjoys the most advanced and stable Islamic democracy, a dynamically developing economy, and the largest corridors of energy resources. The mounting rivalry over regional domination will inevitably heat up competition in Central Asia and the Caucasus.